Decentralising natural resource governance in Ghana: Critical reflections on the artisanal and small-scale mining sector - Hirons, M (Elsevier, 2014)
This paper critically examines the impact of decentralisation on contemporary and future governance arrangements in Ghana's artisanal and small-scale mining (ASM) sector. The sector, while providing valuable employment in rural areas, is beleaguered by environmental and social issues. Proponents of decentralisation argue that re-distributing decision-making authority leads to more responsive, transparent and efficient natural resource management. The analysis presented here, however, demonstrates how weak decentralisation has exacerbated the complex, conflictual and clandestine nature of local resource politics surrounding ASM. If future decentralisation reforms are going to reverse this trend and improve the governance of ASM in Ghana, then facilitating the participation of traditional authorities is imperative. It is argued that doing so requires addressing the reticence regarding the role of chiefs in resource governance; simply ironing out existing technical issues with decentralisation reforms is unlikely to improve the social and environmental performance of ASM in the country. In light of the chronic resource management deficiencies in Ghana, epitomised in the ASM sector, fostering frank political debates on resource governance is becoming urgent.